2016
DOI: 10.1097/scs.0000000000002814
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Analysis of Orbital Region and Age-Related Changes in Adult Women

Abstract: The authors believe that knowing the normal size of the structures in the orbital region and age-related changes will be useful to maintain the facial proportions in the plastic and reconstructive surgery and to protect aesthetic appearance of the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…The characteristic periorbital features of older Korean females are shorter palpebral fissure height, narrower palpebral fissure width, longer eyelid height, shorter binocular width, and smaller palpebral fissure slant. These are consistent with the result by Direk et al 29 , they reported shorter palpebral fissure height, narrower palpebral fissure width, and shorter binocular width in Turkish females aged over 60 years compared with younger (aged 20∼44 years) or middle-aged (45∼59 years) females. Age-dependent shortening of palpebral fissure width was also demonstrated in the Dutch population 30 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The characteristic periorbital features of older Korean females are shorter palpebral fissure height, narrower palpebral fissure width, longer eyelid height, shorter binocular width, and smaller palpebral fissure slant. These are consistent with the result by Direk et al 29 , they reported shorter palpebral fissure height, narrower palpebral fissure width, and shorter binocular width in Turkish females aged over 60 years compared with younger (aged 20∼44 years) or middle-aged (45∼59 years) females. Age-dependent shortening of palpebral fissure width was also demonstrated in the Dutch population 30 .…”
Section: Discussionsupporting
confidence: 92%
“…Longer nasal width is demonstrated in older Korean females when compared with younger counterparts. Aging causes upper maxillary resorption and remodeling of the pyriform aperture 28,29 . As a result, posterior displacement of pyriform aperture occurs 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…l also keeps increasing. Direk et al (2016) through these anthropometric measures found a way to analyze the effect of age on facial morphology [ 12 ]. Under such form these angular measures may undoubtedly help understand some craneofacial abnormalities such as asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…Over our lifespan, for instance, the facial architecture grows through a development (formation) and senescence process. This change may be studied through angular measures [ 12 ]. Face shapes are also used to analyze some abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Lower lid laxity increases with age, and ptosis can occur in older people. Direk et al [18] demonstrated that the palpebral fissure area significantly decreases with age. This finding is consistent with the observed decrease in EEA with age in our study.…”
Section: Fig 5 Eyeball Exposure Area According To Sexmentioning
confidence: 99%